Short-Term Effects of Isotonic Handgrip Exercise on Cardiovascular Autonomic Reactivity in Healthy Young Adolescents - Patel, Nileshkumar H; Shah, Hasmukh D; Shaikh, Wasim A; Singh, Sushil K (National Journal of Community Medicine, 2015)
Background: Objective of the study was to determine the short- term effects of isotonic handgrip exercise on cardiovascular auto- nomic reactivity in healthy adolescents and to find a user friendly exercise which help in reducing blood pressure. Method and Materials: Present study was conducted on 50 young healthy adolescents in the age group of 17–19 years. Isotonic hand- grip exercise was performed for 20 minutes at the rate 12 contrac- tions per minute (2 sec contraction/3 sec relaxation) at an intensity of 30%MVC using Ball-Squeeze Dynamometer. Vascular sympa- thetic reactivity and cardiac parasympathetic reactivity were tested at baseline and during recovery period (Immediate- post-exercise and 1 hour–post-exercise). Result: There were no changes in the parameters (Expiration: In- spiration ratio and Valsalva Ratio) measuring parasympathetic re- activity. Sympathetic reactivity as evaluated by diastolic blood pressure responses to isometric handgrip test (HGT) and cold pres- sor test (CPT) showed no significant decreases. No significant dif- ference was observed in cardiovascular autonomic reactivity dur- ing immediate and 1 hr post-exercise recovery in both boys and girls. Conclusion: It can be concluded that the exercise regime under consideration could not produce any short-term beneficial effects with respect to cardiovascular autonomic reactivity.